Evaluation of 'surgery-friendly' bone scaffold characteristics: 3D printed ductile BG/PCL scaffold with high inorganic content to repair critical bone defects. (1st January 2023) - Huang, Pengren; Yang, Peng; Liu, Keming; Tao, Wei; Tao, Jun; Ai, Fanrong
Abstract: The repair of irregular and complex critical bone defects remains a challenge in clinical practice. The application of 3D-printed bioceramics particle/polymer composite scaffolds in bone tissue engineering has been widely studied. At present, the inorganic particle content of the composite scaffolds is generally low, resulting in poor osteogenic activity. However, scaffold with high inorganic content are highly brittle, difficult to operate during surgery, and cannot be in close contact with surrounding bones. Therefore, it is of great significance to design a 'surgery-friendly' scaffold with high bioceramic content and good ductility. In this study, we used the solvent method to add high concentration (wt% 70%) bioglass (BG) into polycaprolactone (PCL), and polyethylene glycol was used as plasticizer to prepare 70% BG/PCL composite scaffolds with high ductility using 3D printing technology. In vitro experiments showed that the scaffold had good mechanical properties: easy extension, easy folding and strong compressive resistance. It also showed good performance in biocompatibility and osteogenic activity. It was further observed that compared with pure BG or PCL implantation, the scaffold with higher BG content could have more new bone tissue appeared after 12 weeks. All these results indicate that 3D-printed 70% BG/PCL scaffolds have great potential for personalized repair of bone defects.